023 Relapse outcomes with natalizumab Q4W vs switch to Q6W. Issue 6 (27th May 2022) - Butzkueven, Helmut; Kappos, Ludwig; Spelman, Tim; Trojano, Maria; Wiendl, Heinz; Su, Ray; Hyde, Robert; Licata, Stephanie; Ho, Pei-Ran; Campbell, Nolan
Abstract : Introduction: The approved dosing of natalizumab (300 mg infusion every 4 weeks [Q4W]) is associated with risk of progressive multifocal leukoencephalopathy. This analysis from the TYSABRI Observational Program (TOP) compared relapse outcomes in patients who switched to natalizumab every 6 weeks (Q6W) after 1 year of Q4W with patients who remained on Q4W. Methods: Eligible TOP patients had ≥1 year of natalizumab Q4W. Treatment duration-matched Q6W and Q4W patients (191 pairs) were compared by propensity score matching (PSM). Negative binomial model-estimated annualised relapse rate (ARR) and Kaplan-Meier-estimated relapse risk were compared during the post-switch and exposure-matched follow-up periods. Results: After PSM, 135 pairs of Q6W and Q4W patients were included. Mean treatment duration was 4.4 years in both groups. There was no difference in ARR (Q6W: 0.231 [95% confidence interval (CI), 0.145–0.367]; Q4W: 0.254 [0.160–0.402]; P=0.774) or relapse risk (hazard ratio [95% CI], 1.021 [0.583–1.789]; P=0.940) between groups. Conclusions: No significant difference in relapse outcomes was observed between patients who switched 4t6o Q6W and those who remained on Q4W. An ongoing randomized prospective trial of Q4W vs Q6W will inform further on the effectiveness of natalizumab Q6W. Support: Biogen. peiran.ho@biogen.com